Bipolar disorder in the elderly. (December 2011) - Dols, Annemiek; Kupka, Ralph; Kessing, Lars Vedel; Stek, Max; Sajatovic, Martha
Over 1200 participants from a wide array of psychogeriatric disciplines attended the 15th world congress of the International Psychogeriatric Association (IPA) in The Netherlands. In previous years, the meetings and activities of the IPA were strongly focused on research restricted to diagnosis and care of individuals with dementia. In recent years, there has been a shift of attention towards other psychiatric disorders in the elderly such as schizophrenia, substance abuse and bipolar disorder, which were for a long time nearly invisible in the scientific literature. The symposium venue was located in The Hague, a typical Dutch town not far from the coastline and home to several famous international institutions in the field of peace and justice. This successful meeting with the theme 'Reinventing Aging through Innovation, Care, Research, Technology'' was co-chaired by Anne Margriet Pot (Professor of Geropsychology, Amsterdam, The Netherlands) and Frans Verhey (Professor of Neuropsychiatry, Maastricht, The Netherlands). A special symposium on 'Bipolar Disorder in the Elderly'' also took place during the 4-day meeting. This symposium was organized by The Netherlands Psychiatric Association, Faculty of Old Age Psychiatry and is an example of a neglected topic in geriatric mental health and represents the important diverse mental disorders that a large proportion of older adults and their families can experience. The symposium was co-chaired by Max Stek, Professor of Old Age Psychiatry and Chair of the Dutch Faculty of Old Age from The Netherlands and Martha Sajatovic from the USA. Presenting faculty were Ralph Kupka and Annemiek Dols from The Netherlands and Lars Kessing from Denmark.